On the letter “k” in Written Mongolian using for the Sanskrit loan words - G, Ganchimeg (Altaica, 2024)
According to vowel harmony, the letter “k” of the Uyghur-Mongolian alphabet must be used only in the so-called ‘female’ words. In the Sanskrit loan words in Mongolian, however, the letter “ᠭ ” was used in many ‘male’ words. It is one of the influences on the Mongolian languages by the Old Uyghur language scriptures and their Buddhism. Due to the lack of their letter, Uyghurs have created their own way to transcribe Sanskrit words: letter “ᠭ ” for the Sanskrit consonants k, kh, g and gh, letter “ ᠬ ” in the other hand for Sanskrit consonant h. This writing system was taken to the Sanskrit loan words in Mongolian directly and without any changes during the Yuan-period. Монгол бичгийн хэлний санскрит үгийн бичлэг дэх “k” үсгийн тухай Монгол хэлний эгшиг зохицох ёсны дагуу “k” дэвсгэр зөвхөн эм үгэнд хэрэглэгддэг зарчим эртнээс байдаг. Гэтэл монгол хэлэнд орсон санскрит гаралтай үгсийг тэмдэглэхэд энэхүү “k” дэвсгэр эр үгэнд олон тохиолдоно. Энэ бол эртний уйгур хэл, үсэг бичиг жич уйгуруудын бурхны шашны монгол хэлэнд үзүүлсэн нөлөөний илрэл юм. Санскрит хэлний k, kh, g хийгээд gh зэрэг гийгүүлэгчийг уйгур үсгийн “k” дүрсээр тэмдэглэж, үүний зэрэгцээ h гийгүүлэгчийг “k” дүрсээр тэмдэглэх бичлэгийн тогтолцоог уйгурууд зохиожээ. Энэ тогтолцоо нь эртний монгол бичгийн хэлэнд шууд уламжлагдаж орсон аж. Түлхүүр үг: санскрит гаралтай үг, “k” дэвсгэр, монгол бичиг, уйгур бичгийн хэл